One-Step, Low-Cost, Operator-Friendly, and Scalable Procedure to Synthetize Novel Tetrazolopyrimidinylbenzopyran-2-ones by Benign Protocol - Ahmed, Eman A.; Khodairy, Ahmed; Abd El Aleem Ali Ali El-Remaily, Mahmoud; Ahmed, Abdelraheem M. (Current Organic Chemistry, 2022)
New coumarin chalcones 3j-p were conveniently obtained in high yields via Claisen-Schmidt condensation reaction, when acetyl coumarin 1 reacted with 3-aryl-1-phenyl pyrazole-4-carbaldehydes 2j-p in boiling ethanol in the presence of triethyl amine as a catalyst. Also, two synthetic pathways were afforded for the synthesis of novel tetrazolo[1,5- a]pyrimidinyl-2H-chromen-2-ones 5a-p. The first pathway is a multistep process including formation and separation of chalcones, which then were allowed to react with 5-aminotetrazole 4. While, the second pathway is a highly efficient one-pot three-component condensation reaction of 3-acetyl coumarin 1, aromatic aldehydes 2a-p and 5-aminotetrazole 4 under green and mild reaction conditions by using acetic acid (AcOH) as a catalyst and solvent. The molecular structure of products was established on the basis of their NMRs, IR and elemental analysis data. Solvent optimization was carried out in the reaction producing 3-(5-Phenyl-4,5-dihydrotetrazolo[1,5- a]pyrimidin-7-yl)-2H-chromen-2-one (5a). The advantages to using environmental-friendly acetic acid are simple operation, short reaction time, high efficient (97%), operationally facile and wide tolerance of starting materials.
Keywords: condensation